Effect of Silica Nanoparticles Modification on the Thermal, Structural, and Decomposition Properties of a β‐Nucleated Poly(propylene‐co‐ethylene) Matrix. Issue 9 (19th March 2014) - Papageorgiou, Dimitrios G.; Vourlias, George; Bikiaris, Dimitrios N.; Chrissafis, Konstantinos
<x xml:space="preserve">Abstract</x> In the current investigation, nanocomposites containing a β‐nucleated poly(propylene‐co‐ethylene) (PPR) matrix filled with untreated (SiO2) and methacrylate‐modified silica nanoparticles (SiO2‐MAA) are prepared. Transmission electron microscopy (TEM) reveals the improvement in the quality of dispersion due to the surface modification of the nanoparticles. Also, from differential scanning calorimetry (DSC) and X‐ray diffraction (XRD), it is found that the β‐nucleating agent and silica nanoparticles work synergistically in order to increase the relative β‐content in the nanocomposite samples. The thermal stability of each samples is evaluated by means of thermogravimetric analysis (TGA) and the enhancement of the thermal stability of the nanocomposites is attributed to the nanoconfinement of the macromolecular chains caused by the presence of the fillers. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>